Parametric study of flyash based geopolymer concrete - Kumar Das, Sourav (International Journal of Engineering and Technology, 2018)
With the growth of civilization the demand of cement concrete is increasing rapidly which increase the production of cement and abolishing the natural source of limestone. Also contributing a lot to the global warming by generating huge amount of carbon-di-oxide. Therefore the present study concentrate on the production of concrete using the geopolymerization technology which replaces cement fully by fly ash, a waste material and alkali solution. India is presently producing approximately 190 million tons of fly ash every year from moreover 145 power plants. Present research is focused on the different parameters which are curing temperature, ratio of sodium silicate to sodium hydroxide, molarity of sodium hydroxide, curing type and the results have been studied and discussed. Previous works emphasis that only the use of fly ash as the base material confine the concrete to be heat cured which limits the applicability of geopolymer concrete to cast-in-situ conditions. So some proportion of flyash is replaced by ground granulated blast furnace slag (GGBFS) and the effect on compressive and tensile strength is observed. Ambient temperature dry curing was done without any water when some proportion of fly ash was replaced by GGBFS. The ratio of sodium silicate solution to sodium hydroxide solution by mass was kept fixed at 2.5 and the concentration of sodium hydroxide was kept 14M. The ratio of flyash to alkali solution was kept 0.35 & 0.40. Replacing 40% of Flyash by GGBFS and keeping the concentration of NaOH as 14M at ambient temperature, the compressive strength encountered was 40 MPa.Â